Specific Treatment of Elderly Pilgrims on Hajj According to the Hadith ; The Approach of Mukhtalif Ahadis - Masyithah Mardhatillah (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2019)
Most of Indonesian hajj pilgrims are elderly due to approximately 23 years waiting period. This paper aims to elaborate specific treatment of elderly pilgrims according to the hadith. Some hadith imply indirect prohibition to perform hajj by themselves while others still motivate the hajj in a hard condition. Using the approach of mukhtalif ahâdits, this paper seeks to answer three questions. First, how did hadith say about specific treatment of elderly hajj pilgrims. Second, how to deal with two groups of hadith which slightly look different. Third, how is proper contextual interpretation on the hadith in Indonesian contemporary life. The data compilation is through literature reviews and interviews. Then, the two groups of hadith are compromised using a method called al-jam’u wa al-tawfiq. It truns out that the first hadith applies for those who can’t really perform the hajj while another is for those with physical problems but could still stand for hajj using some facilities and policies. Those all lead to an inevitable need for a special hajj manasik for elderly so they could perform the hajj with better preparation. (Dengan waktu tunggu keberangkatan kurang lebih 23 tahun, sebagian besar jama’ah haji Indonesia adalah lansia. Penelitian ini mendiskusikan pandangan hadist soal perlakuan khusus terhadap jama’ah lansia. Beberapa hadist menyiratkan imbauan untuk tidak melaksanakan haji secara langsung, sedang beberapa lain tetap memotivasi pelaksanaan haji dalam keadaan sulit sekalipun. Dengan pendekatan mukhtalif ahâdits, penelitian ini fokus menjawab tiga persoalan. Pertama, bagaimana pandangan hadist terhadap jamaah lansia. Kedua, bagaimana mengompromikan dua (kelompok) hadist yang sekilas tampak berbeda. Ketiga, bagaimana interpretasi kontekstual hadist-hadist tersebut dalam konteks Indonesia dewasa ini. Data penelitian didapat melalui penelusuran pustaka dan wawancara. Dua kelompok hadist kemudian dikompromikan dengan metode al-jam’u wa al-tawfiq. Hasilnya menunjukkan bahwa hadist pertama berlaku bagi jama’ah yang benar-benar tidak bisa melaksanakan haji, sedang yang kedua adalah bagi mereka dengan kemampuan fisik yang minim namun masih memanfaatkan fasilitas dan kebijakan yang ada. Dari situ, adanya sebuah manasik (kelas haji) khusus lansia di Indonesia menjadi keniscayaan agar jama’ah lansia dapat semakin maksimal memersiapkan dan melaksanakan haji)